2001
DOI: 10.2754/avb200170010091
|View full text |Cite
|
Sign up to set email alerts
|

Groups of Honey - Physicochemical Properties and Heavy Metals

Abstract: The aim of the study was to obtain the physicochemical characteristics and the content of Cd, Pb, Hg, Cu and Zn in three groups of honey (blossom, blends and honeydew). Physicochemical constituents were examined according the European Honey Commission recommended methods and heavy metals were determined by atomic absorption spectrometry. Among the groups of honey significant differences in the amount of mineral substances, pH, electrical conductivity (P < 0.01) and free acidity (P < 0.05) were found. Differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
27
2
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 10 publications
6
27
2
2
Order By: Relevance
“…The pH value of the honeys ranged from 3.65 to 4.53. These values were similar to those obtained by other authors (2,6,14,26,31,42,43,48,51,52).…”
Section: Resultssupporting
confidence: 82%
“…The pH value of the honeys ranged from 3.65 to 4.53. These values were similar to those obtained by other authors (2,6,14,26,31,42,43,48,51,52).…”
Section: Resultssupporting
confidence: 82%
“…The moisture content varied from 15.26 % in the honeydew honey from west region to 17.65 % in the honeydew honey from Slovakian west region (Table II) Similarly results were found in the blossom honey (15.9 ± 1.2 %), blends honey (15.9 ± 1.2 %) and ho neydew honey (15.6 ± 1.7 %) in the Czech Republic (Če-lechovská and Vorlová, 2001). The moisture content in Slovak honey varied from 16.00 to 19.80 % (Kačá-niová et al, 2009).…”
Section: Resultssupporting
confidence: 56%
“…Data on the PAHs content in honey are very rare, nevertheless, some authors reported high concentrations of PAHs in honey (Dobrinas et al 2008). Trace concentration of metals in honey and their high variability are dependent very strongly on the botanical and geographical origin, and less on the climatic and seasonal criteria (Čelechovská and Vorlová 2001). Remarkably elevated values of trace elements in honey were reported in samples from industrial and otherwise polluted areas (Bogdanov et al 2007).…”
Section: Persistent Organic Pollutants Toxic Elements Hplc Atomic mentioning
confidence: 99%